The Next Decade Ahead. Issue 1 (29th December 2022) - Mellmann, Dörthe
Abstract : The Next Decade Ahead, AsianJOC is looking for further growth after the past achievements until its 10 th anniversary year in 2022. Check out the Editorial for newly onboarded ECAB and IAB members as well as for news on Special Collections.